2012
DOI: 10.1016/j.jval.2012.03.452
|View full text |Cite
|
Sign up to set email alerts
|

PMH7 Impact of Long-Acting Injectable Versus Oral Antipsychotics on Rehospitalization Rates and Emergency Room Visits among Relapsed Schizophrenia Patients

Abstract: adjusting for baseline factors (age, sex, race, region, metropolitan statistical area, family income, and health insurance coverage) using regression model statistics (adjusted R2). RESULTS: The overall prevalence of pediatric ADHD was 2.47% (n ϭ 5.82 million). Most of the children were boys (68%), White (84%) and had private health insurance (62%). Overall mean annual expenditure was $ 4145.87. Adjusted R2 for the baseline model was 0.1130. When different comorbidity measures were added to the baseline model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the same vein, the electronic records of patients medicated with LAI SGAs were compared with oral APs over a 30-month period revealed that LAI SGAs were associated with significantly lower mean number of hospitalizations, emergency room visits and fewer hospitalization days compared with oral APs. 297 Mirror-image studies evaluate the effect before versus after initiation of LAI treatment, with patients serving as their own controls. Mirror image studies published in the early 1970s provided the first clinical evidence favoring LAIs versus oral APs in terms of frequency and duration of hospitalizations.…”
Section: Long Acting Versus Oral Antipsychotic Medicationmentioning
confidence: 99%
“…In the same vein, the electronic records of patients medicated with LAI SGAs were compared with oral APs over a 30-month period revealed that LAI SGAs were associated with significantly lower mean number of hospitalizations, emergency room visits and fewer hospitalization days compared with oral APs. 297 Mirror-image studies evaluate the effect before versus after initiation of LAI treatment, with patients serving as their own controls. Mirror image studies published in the early 1970s provided the first clinical evidence favoring LAIs versus oral APs in terms of frequency and duration of hospitalizations.…”
Section: Long Acting Versus Oral Antipsychotic Medicationmentioning
confidence: 99%